Unraveling the hidden function of a stabilizer in a precursor in improving hybrid perovskite film morphology for high efficiency solar cells. Issue 3 (5th February 2016) - Xiao, Zhengguo; Wang, Dong; Dong, Qingfeng; Wang, Qi; Wei, Wei; Dai, Jun; Zeng, Xiaocheng; Huang, Jinsong
Abstract : The precursor purity is critical for the perovskite film morphology and solar cell device performance. Abstract : The morphology of the organometal trihalide perovskite (OTP) plays a critical role in the performance of solar cell devices. Nevertheless it has been frequently reported that the morphology of OTP films tends to be different in different laboratories even with the same film preparation procedure, which makes it very difficult to compare and understand the material and device physics. Here, we unravel a critical role of the H3 PO2 stabilizer in HI, which has been largely ignored, in controlling the morphology of the perovskite films. The H3 PO2 stabilizer in HI solution introduces MAH2 PO2 impurities into the synthesized MAI (non-purified MAI) by reacting with methylamine (MA) aqueous solution. MAH2 PO2 impurities can slow down the overall crystallization process of perovskite by forming an intermediate phase of Pb(H2 PO2 )2 . Both MAH2 PO2 and Pb(H2 PO2 )2 impede the fast reaction of PbI2 and MAI, resulting in highly uniform and smooth perovskite films with larger grain sizes. The recrystallization of non-purified MAI can remove the MAH2 PO2 impurity and form purified MAI, which however results in rough and non-uniform perovskite films. Uniform and smooth perovskite films can also be obtained by directly adding artificially synthesized MAH2 PO2 into the purified MAI precursor. This study also suggests Pb(H2 PO2 )2 to be a new precursor to form high quality perovskite films.